Filogenia molecular da subtribo Disynaphiinae (Eupatorieae: Asteraceae),tratamento taxonômico e sinopse de Symphyopappus, e anatomia floral do clado Grazielia/Symphyopappus - Eric Koiti Okiyama Hattori (2013)
Eupatorieae is one of the main tribes in the Asteraceae, and its generical and subtribal classification has suffered changes in the last 40 years, based on floral microcharacters. The most important was the splitting of Eupatorium in more than 80 genera. Nevertheless, recent phylogenetic studies with South American species have revealed that these groups are non-natural, mostly the proposed subtribes. Disynaphiinae is known by its consistency in number of flowers per head and the restrict geographic distribution in South America. Symphyopappus is known by its wide morphological range, as the venation of leaves, the presence of trichomes in receptacle and the number of series of bristles in pappus. Nevertheless, the relationship among these genera is not known; not rarely, in the main herbaria of Brazil, are found Symphyopappus with confused determinations; furthermore, little is known about the floral anatomy in Eupatorieae, as subsidy to phylogenetic studies. Thus, the objectives of the present thesis are: the inference of relationship among the genera in Disynaphiinae based on molecular phylogenetic study; present a key of identification for Symphyopappus, with a discussion about the main morphological characters through the taxonomic treatment and synopsis;a key for Campovassouria and Raulinoreitzia through the revisional study; and assess the floral anatomical characters of Grazielia and Symphyopappus. The molecular phylogenetic study revealed the paraphyletism of Disynaphiinae, as well as the Symphyopappus. Based in morphology, it was necessary the synonymization of Symphyopappus angustifolius and S. reticulatus under S. brasiliensis. On the other hand, it is proposed a new species, endemic to cangas of the Iron Quadrangle, and a new name based in S. apurimacensis, a name not validly published. By this way, are recognized 13 species in Symphyopappus in the present study. To Campovassouria, it was necessary the recombination of Grazielia brevipetiolata, so that are recognized three species to this genus. The vasculature of internal involucral bract, the shape of epidermal cells in sytle branch, and the vasculature of ovule are anatomical characters that corroborate the position of S. compressusand S. lymansmithii included in the Grazielia clade, obtained in the phylogenetic study.